Studies on 5-FU concentration in serum and prostate cancer tissue after oral administration of UFT - Shinoda, I (Hinyokika kiyo. Acta urologica Japonica, 1991)
The serum, urine and tissue concentrations of 1-(2-tetrahydrofuryl)-5-fluorouracil (FT), 5-fluorouracil (5-FU) and uracil were estimated in 11 patients with prostate cancer (4 cases treated by total prostatectomy and 7 cases by transurethral resection (TUR-P) after oral administration of UFT. The concentration of FT, 5-FU and uracil in the tumor tissue (micrograms/g) were 5.920 +/- 5.902, 0.018 +/- 0.012 (T/S; 2.20) and 7.785 +/- 4.151 in 4 patients treated by total prostatectomy and 1.943 +/- 1.355, 0.024 +/- 0.010 (T/S; 1.46) and 4.616 +/- 2.848 in 7 patients treated by transurethral resection of prostate. The concentrations of FT, 5-FU and uracil in the tumor tissue did not increase as compared with those in normal tissue in 4 cases treated by total prostatectomy